Petroleum System Evaluation of Kutubdia Area, Bengal Basin, Offshore Bangladesh - Hossain, Abdullah (Bulletin of Earth Sciences of Thailand, 2021)
Kutubdia well was the first offshore gas discovery in Bengal shelf, Bangladesh in 1976 and yet the petroleum system of Kutubdia and the surrounding area is still not well understood. This study attempts to integrate all parameters related to the petroleum system to better understand the hydrocarbon generation and migration in the Kutubdia area as well as reservoir distributions and trapping styles. Depositional environments were determined from well log response and seismic facies analysis. Hydrocarbon bearing pay sands were deposited in a deltaic environment determined from well log coarsening upward response and high amplitude parallel reflections on seismic. Seismic facies analysis was used as a significant tool to identify formation boundaries on the seismic. The Top of Bokabil is a significant erosional surface in this area which may correlate with the Messinian regression in the late Miocene times. Horizon interpretation was used to make structural maps of source and reservoir rock intervals. The formation of anticlinal structures was in the late Miocene to early Pliocene evidenced by seismic data which shows thinning over the anticlinal structures during this time. Hydrocarbon bearing pay sands within the Middle Bokabil formation in the Kutubdia well show high gamma ray response due to presence of radiogenic material. High gamma ray and porosity of the hydrocarbon pay sand implies that reservoir sands are poor quality. Source rock for the Kutubdia area is within the underlying Bhuban formation which is located within the gas window and major vertical migration occurred due to the thrusting nature of the structural formation. Reserve calculations were carried out using both shallow-deep resistivity separations and single deep resistivity methods which provide a substantial range of potential reserve estimations for the Kutubdia discovery.